Critical Interpretation of Hybridisation in Korean Cinema: Does the Local Film Industry Create “The Third Space”? - Jin, Dal Yong (Javnost-The Public, 2010)
This paper examines the fundamental assumptions of the concept of cultural hybridity in understanding the swift growth of Korean popular culture, especially films. It investigates whether hybridity, as a cultural globalization perspective, has generated new possible cultures, which are free from western dominance, by analyzing the hybridised Korean fi lms. Unlike previous studies emphasising the crucial role of hybridisation in creating the third space, this paper empirically argues that the hybridisation process of the local popular culture is heavily infl uenced by Western norms and formats, and newly created local cultural products are rather representing Western culture, instead of unique local culture. It fi nally discusses the reasons why hybridity cannot adequately explain local cultures and identify some issues we have to consider in employing hybridity in interpreting globalisation.